Parrhesía e produção de subjetividade em Arnaldo Antunes : escrita, autoria e poder - Lopes, Sirlene Cíntia Alferes (2015)
Considering that the practice of parrhesia is committed to truth-telling, and in relation to art this concept is reformulated, I analyze productions of Arnaldo Antunes in this thesis, taking into account the written notions of authorship, power, parrhesia, subjectivity, and identity from the perspective of Foucault s discourse. I established names as input for analysis, conceived as that which functions as specifier and differentiator of meanings, always tangent by the system (language), by subject, and by history: the tripod of sustainability of construction of the senses. I observed the recurrence of names in arnaldian works (Che Guevara, Simone de Beauvoir, Pinochet, Lao Tzu, Stalin, Hitler, etc.), which made me inquire about the ability to study these productions from the perspective of Foucault s discourse. To constitute the corpus of this study, I resorted to the works 40 escritos, Como é que chama o nome disso, Outros 40, and the Official site of Arnaldo Antunes (www.arnaldoantunes.com.br). I proposed the hypothesis that there would be arnaldian productions in a veiled way of discourses materialization that would throw-open power relations and would enable the practice of parrhesia and the production of subjectivity. This throwing-open of power relations would take place through the opposition between discourses, which would materialize themselves through the memory, immersed in the names in the tension between the spoken and unspoken via speech, enabling even in certain cases, the construction of subject identities. As theoretical and methodological subsidy, I based the study in Foucault s L archéologie du savoir1, from the notion of speech as the elementary unit of discourse (p.90). Thus, it was possible to collate statements in order to show that parrhesia, in the present day, takes place differently from the Greek era. However, it is still a means of commitment to truth (as a construct), in a comparison of historical, social, and cultural issues from what is permitted by the arts: a privileged place for transgression. In the first chapter, I discussed aspects of the study of arnaldian productions and I justified the choice for analyzing these productions from the power relations postulated in Foucault s texts. In the second chapter, I traced the theoretical and methodological path in order to observe some concepts that were key to the development of this research to be precise: appellative, articulation, statement, speech, historical discontinuity, writing, authorship, relational character of the power and forms of resistance, parrhesia, production of subjectivity, and other discussed concepts that were bound to the former concepts (the being of language, memory, history, subject, identity, difference, etc.), based primarily on Foucault s texts and authors who join the Discourse Analysis from the perspective of that author. In the third chapter, I analyzed arnaldian productions making comparisons with the principally addressed concepts, in order to reach the goal of this thesis and to see if the hypothesis could firmly stand. Finally, I resumed the discussion of arnaldian production and its relation to contemporary literature, as well as the reconfiguration of the notion of parrhesia and its relation to subjectivity, writing, authorship, and the power from the productions of Arnaldo Antunes.